Nutritional Assessment Methodologies: Challenges and Opportunities for the Full Realization of the Right to Food and Nutrition - Salcedo Fidalgo, Hernando; Morales, Juan Carlos (Frontiers in Nutrition, 2019)
The structural isolation of nutrition from the human right to food has resulted in the technicalization and medicalization of the meaning and practice of nutrition, including in the field of nutritional assessments, which has led to the construction of public policies that lack a holistic perspective with a rights-based approach. Two main categories of nutritional assessments have been anthropometric measurements and nutritional profiles evident in the WHO and PAHO proposals related to the nutrition of children. In this paper, we present a critical discussion on the production and uses of both instruments in the evaluation of the growth and development of children and in the generation of global recommendations in public health with the objective of proposing alternatives for the measurement of malnutrition in communities affected by violations of the human right to food and nutrition. Our approach focuses on the construction not only based on the calorie-energy needs of the human body but also on food as a social, cultural and political process. It thus becomes an invitation to rethink nutrition from the notion of the right to food to the implementation of research from a participatory action.